Towards Peaceful Islam: Jemaat Ahmadiyah Indonesia (JAI) as A New Social Movement - Fadhillah, Nuurul Fajari (UI Scholars Hub, 2017)
The Ahmadiyya religious group has been present in Indonesia since the 1920s. The reli- gious group is divided into two different subgroups, namely Gerakan Ahmadiyah Indone- sia (GAI) and Jemaat Ahmadiyah Indonesia (JAI). In the reform era, the JAI community has to face a less favorable situation. The Heresy Fatwa issued by Majelis Ulama Indonesia (MUI) in 1980 had put this group into an even more difficult position. The reform era government seemed to give a greater opportunity for anti-Ahmadiyya dominant Islamic groups to commit violence towards this group. JAI communities in various areas expe- rienced various forms of discrimination and violence, such as the closure of mosques, assaults, and expulsions. Dealing with this situation, JAI,with their belief of peaceful Islam, tried to develop persuasive cultural approaches to survive and subsequently to be accepted by the society. This article aims to analyze JAI as a new social movement based on their cultural approaches to maintain their existence in the society. These efforts reflect the occurrence of the revival of collective identity, which also becomes the characteristic of this movement.